Ніж з тамгообразним знаком з могильника Нейзац у Криму - Храпунов, І.М. (Археологія, 2004)
У статті публікується ніж унікальної форми, на руків'ї якого було прокреслено тамгообразний сарматський знак. Поховальний комплекс з цією знахідкою датується ІІІ ст. н. е. В статье публикуются результаты раскопок подбойной могилы 194 из некрополя Нейзац, расположенного в Центральном Крыму. Конструкция погребального сооружения и инвентарь свидетельствуют о принадлежности комплекса к позднесарматской археологической культуре. Захоронение в могиле датируется 111 в. до н. э. Особый интерес представляет уникальной формы нож, на костяной рукояти которого процарапан тамгообразный знак. The article publishes the excavation results of an undercut grave N 194 from the Neizats necropolis located in the Central Crimea. The constructional features of the burial structure and the grave goods relate the assemblage to the Late Sarmatian archaeological culture. The burial in the grave is dated back to the 3,J century B.C. A uniquely shaped knife with a tamaga-likc symbol scratched on its bone handle is of particular interest.